Does the morphology of cutaneous melanoma help to explain the international differences in survival? Results from 1 578 482 adults diagnosed during 2000–2014 in 59 countries (CONCORD‐3). (28th July 2022) - Di Carlo, Veronica; Stiller, Charles A.; Eisemann, Nora; Bordoni, Andrea; Matz, Melissa; Curado, Maria P.; Daubisse‐Marliac, Laetitia; Valkov, Mikhail; Bulliard, Jean‐Luc; Morrison, David; Johnson, Chris; Girardi, Fabio; et al.
Abstract: Background: CONCORD‐3 highlighted wide disparities in population‐based 5‐year net survival for cutaneous melanoma during 2000–2014. Clinical evidence suggests marked international differences in the proportion of lethal acral and nodular subtypes of cutaneous melanoma. Objectives: We aimed to assess whether the differences in morphology may explain global variation in survival. Methods: Patients with melanoma were grouped into the following seven morphological categories: malignant melanoma, not otherwise specified (International Classification of Diseases for Oncology, third revision morphology code 8720), superficial spreading melanoma (8743), lentigo maligna melanoma (8742), nodular melanoma (8721), acral lentiginous melanoma (8744), desmoplastic melanoma (8745) and other morphologies (8722–8723, 8726–8727, 8730, 8740–8741, 8746, 8761, 8770–8774, 8780). We estimated net survival using the nonparametric Pohar Perme estimator, correcting for background mortality by single year of age, sex and calendar year in each country or region. All‐ages survival estimates were standardized using the International Cancer Survival Standard weights. We fitted a flexible parametric model to estimate the effect of morphology on the hazard of death. Results: Worldwide, the proportion of nodular melanoma ranged between 7% and 13%. Acral lentiginous melanoma accounted for less than 2% of all registrations but was more common in Asia (6%) and Central and South America (7%). Overall, 36% of tumours were classified as superficial spreading melanoma. During 2010–2014, age‐standardized 5‐year net survival for superficial spreading melanoma was 95% or higher in Oceania, North America and most European countries, but was only 71% in Taiwan. Survival for acral lentiginous melanoma ranged between 66% and 95%. Nodular melanoma had the poorest prognosis in all countries. The multivariable analysis of data from registries with complete information on stage and morphology found that sex, age and stage at diagnosis only partially explain the higher risk of death for nodular and acral lentiginous subtypes. Conclusions: This study provides the broadest picture of distribution and population‐based survival trends for the main morphological subtypes of cutaneous melanoma in 59 countries. The poorer prognosis for nodular and acral lentiginous melanomas, more frequent in Asia and Latin America, suggests the need for health policies aimed at specific populations to improve awareness, early diagnosis and access to treatment. What is already known about this topic? The histopathological features of cutaneous melanoma vary markedly worldwide. The proportion of melanomas with the more aggressive acral lentiginous or nodular histological subtypes is higher in populations with predominantly dark skin than in populations with predominantly fair skin. What does this study add? We aimed to assess the extent to which these differences in morphology may explain international variation in survival when all histological subtypes are combined. This study provides, for the first time, international comparisons of population‐based survival at 5 years for the main histological subtypes of melanoma for over 1.5 million adults diagnosed during 2000–2014. This study highlights the less favourable distribution of histological subtypes in Asia and Central and South America, and the poorer prognosis for nodular and acral lentiginous melanomas. We found that later stage at diagnosis does not fully explain the higher excess risk of death for nodular and acral lentiginous melanoma compared with superficial spreading melanoma. Abstract : Linked Comment: C.M. Olsen. Br J Dermatol 2022; 187 :284.